DIGITALIZATION OF WEBSITE-BASED KNOWLEDGE MANAGEMENT AT THE CLASS I IMMIGRATION OFFICE OF TPI CILACAP - P. Assiroj; G.B Hertantyo; R.A Sriwijaya (Polteknik Imigrasi, 2022)
Technological developments have made the use of information technology currently widely applied in the service process, but not only for public services, but also for internal immigration offices. Knowledge management must be applied to employees for refreshment and to carry out rotations, mutations to increase employee Human Resources and the competency level of employees. The process of employee rotation, employee transfer, and recruitment of new employees that is not matched by adequate knowledge management can result in a lack of competence of employees when transferred. The implementation of technological developments and knowledge management provides an overview of website-based application design at Cilacap Immigration Office using the waterfall model SDLC method. The result of this research is a prototype of employee knowledge management application, which contains employee knowledge and employee performance objectives or SKP.